PENGARUH KUALITAS AUDITOR PADA MANAJEMEN LABA SAAT PERGANTIAN CHIEF EXECUTIVE OFFICER (CEO) - Sudariyanta, Ridwan Agung M.; Sukartha, I Made (E-Jurnal Akuntansi; Vol 11 No 1 (2015), 2015)
Good or poor performance of the company is reflected in all the effort and hard work in managing the company 's top management in order to achieve the main objectives of the company. Companies that are experiencing a decline for the sake of determining its future, making CEO turnover as the best strategy that can be chosen. The purpose of this research was conducted, is : 1 ) to test the earnings management practices that triggered the CEO turnover in companies listed on the Indonesian Stock Exchange in the study period of 2002 through 2012, and 2 ) examine the effect of auditor quality on earnings management practices. With discretionary accruals as a proxy for earnings management based on the Modified Jones model and tested using independent sample t-test showed the results of research that occurred earnings management practices by increasing earnings in the change of CEO. The quality auditors in this study were tested by simple linear regression analysis showed the effect on earnings management, which shows the results that the increasing quality of the auditor will lower earnings management practices.
Keywords: earnings management , discretionary accruals , CEO turnover , quality auditors